Community survey on noise impacts induced by 2 MW wind turbines in China. Issue 4 (December 2016) - Song, Kai; Di, Guoqing; Xu, Yaqian; Chen, Xingwang
In order to investigate the noise impacts of wind turbines with a high single-machine capacity (2 MW) on the residents living around, a face-to-face questionnaire survey was conducted. The moderating factors of noise annoyance, noise exposure–response relationships as well as noise impacts on sleep and self-reported health were investigated. Results showed that noise sensitivity, attitude towards wind turbines' visual impact on the landscape, general opinion on wind turbines and noise intensity had statistically significant impacts on annoyance due to wind turbine noise. Compared with wind turbines with lower single-machine capacity in relevant studies, those with higher single-machine capacity in this study induced higher annoyance at the same L den, which was relative to the visibility of wind turbines, background noise levels of wind farm area, etc. Noise sensitivity, noise annoyance and noise intensity, which had no significant correlation with self-reported health effects, were statistically significantly correlated with sleep disturbance on respondents.